Peran Program Kartu Indonesia Pintar Dalam Peningkatan Akses Pendidikan Bagi Siswa Dari Keluarga Kurang Mampu - Kholifah Nur Khasanah kholifah; Nur Khasanah (CV. AKIRA JAVA BULU, 2026)
The Indonesia Smart Card (KIP) Program is one of the government's efforts to guarantee the right to education for children from underprivileged families. This study aims to identify the role of KIP in expanding access to and equitable distribution of education in Indonesia. The method used is a literature study (library research) by examining various sources such as scientific journals, books, and official reports from the Ministry of Education, Culture, Research, and Technology and the Central Statistics Agency (BPS). The results of the study show that KIP contributes to reducing dropout rates and increasing student participation in education, especially in areas with high poverty rates. Based on 2025 data, more than 2.7 million students are registered as beneficiaries of this program. Although there are still obstacles in data collection and distribution of assistance, KIP has proven to be a concrete step in realizing educational equity and social justice in Indonesia.